Translation and validation of the upper extremity functional index-15 (UEFI-15) malay version / Stephennus Stanley Chiam - Chiam, Stephennus Stanley (2024)
Upper Extremity Functional Index (UEFI) is a valid Patient-Reported Outcome Measures (PROMs) to assess upper extremities function in musculoskeletal disorders. There were still no translations of any UEFI versions into Malay language. Thus, a cross-cultural translation of UEFI-15 is needed to provide clinicians and researchers in Malaysia access to a valid and reliable tool in our own cultural context and language. This study was divided into two phases. Phase one aimed to systematically review and appraise the clinical utility and psychometric properties of all available versions of UEFI. Phase two aimed to cross-culturally translate and validate the UEFI-15 into the Malay language. For phase one, a systematic review was conducted using the PRISMA guideline. A comprehensive search was conducted using Scopus, Web of Science, PubMed, CINAHL, MEDLINE, and AMED databases. For phase two, a cross-sectional study design was used. Ten occupational therapist or lecturer with clinical experience handling patients with upper extremity disorder participated in the content validity testing. Ten participants with musculoskeletal disorders of upper extremities participated in the face validity testing. 150 participants with musculoskeletal disorders of the upper extremities referred to the Occupational Therapy Department at Hospital Queen Elizabeth and Hospital Queen Elizabeth 2 were psychometrically tested to establish the reliability and validity properties of the Malay version of UEFI-15. The results of phase one of this study showed that UEFI was utilised in five populations: musculoskeletal disorder, breast cancer, post-operative, stroke, and burn. Unsurprisingly, UEFI was most frequently used in the musculoskeletal disorder population. All available UEFI versions were valid and reliable for the musculoskeletal disorder population. UEFI was also proven reliable and valid for the breast cancer population. The results of phase two indicated that the Cronbach’s alpha coefficient for the UEFI-15 Malay version was reported as excellent (0.965). The ICC of the UEFI-15 Malay version was reported 0.982, considered excellent. Convergent validity, UEFI-15 Malay version demonstrated a strong negative correlation with MVDASH, with a Pearson correlation coefficient value of -0.872. In conclusion, UEFI is mainly used in the musculoskeletal disorder population. All available versions of UEFI were proven reliable and valid. The UEFI-15 Malay version was proven valid and reliable in the musculoskeletal disorder of the upper extremities population. This study holds implications for clinicians and researchers by providing evidence on the utilisation and psychometric properties of all available versions of UEFI. It also provides evidence of its validity and reliability.